Answer:
2
Step-by-step explanation:
-(-1) + (-7) + (2) - (-4) - (-2) =
= 1 + (-7) + 2 + 4 + 2
= -6 + 2 + 4 + 2
= -4 + 4 + 2
= 0 + 2
= 2
Answer:
Step-by-step explanation:
All other things being equal, spinner A is fine. It is a fair spinner.
Spinner B is not fair. Players 1 and 3 have only 1 number each. Player 2 on the other hand, has 2 numbers that work for him. If player 2 puts in two dollars and players 1 and 3 one dollar each, that should even up the odds. Now you want it just to be fair. So I think player 2 has to put up 2 dollars and players 1 and 3 each put up one. The pot is 4 dollars each time it is played.
Spinner 3 is not fair either. Player one has 2 chances. Player 2 has 3 chances and player 3 has but one chance. There are 6 chances in all. Player 1 should put up 2 dollars to play player 1 should put up 3 dollars and player 1 should put up 1 dollar.
Answer:
3 point in draw
Step-by-step explanation:
because the trinidad netballer draw and got 3 points
Answer:
8.5%
Step-by-step explanation:
I=PRT
85= 2000*r*0.5
85=1000r
0.085=r
8.5%
f(x) = (x - 4)^2 - 1
g(x) = -(1/4) ( x - 4)^2 + 4
both the x and y values have to be the same. Start with the y values
f(x) = g(x)
(x - 4)^2 - 1 = -(1/4) (x - 4)^2 + 4 Add 1 to both sides.
(x - 4)^2 = -(1/4) (x - 4)^2 + 5 Add 1/4(x - 4)^2 to both sides.
(5/4) (x - 4)^2 = 5 Divide by 5/4 on both sides.
(x - 4)^2 = 5//(5/4)
(x - 4)^2 = (5/1)//5/4 Invert the second fraction and multiply
(x - 4)^2 = 5/1 * 4/5
(x - 4)^2 = 4 The 5s cancel
(x - 4)^2 = 4 Take the square root of both sides.
(x - 4) = +/- 2 Add 4 to each answer. Start with +2 on the right.
x - 4 + 4 = 2 + 4
x = 4 + 2 = 6
The x value that makes f(x)- g(x) = 0 is x = 6 The point is (6,3) answer.
Answer C.
================================================
You do not need this next part. It is just for completeness.
x - 4 = - 2
x = 4 -2
x = 2
What are the y values for these 2 x values?
y = (x - 4)^2 - 1
y = (6 - 4)^2 - 1
y = 4 - 1
y = 3
The point where f(x) - g(x) = 0 is (6,3) <<<<<< Answer 1
The second point is
y = (x - 4)^2 - 1
y = (2 - 4)^2 - 1
y = (-2)^2 - 1
y = 4 - 1
y = 3
The second point is (2,3). Answer 2
Note the y values are the same. You might expect that.